USING PICTURE SERIES TO IMPROVE THE SPEAKING ABILITY OF THE FIRST YEAR STUDENTS OF SMPN 2 MERBAU - Mashuri Mashuri; Eliwarti Eliwarti; Indah Tri purwanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This Research is classromm action research that was conducted based on the problem occurred at seventh grade students of SMPN 2 Merbau; namely the students were lack in speaking that influence them got poor scor in test. Therefore, this research was aimed at studying the improvement on the ability of seventh grade students of SMPN 2 Merbau in speaking by using picture series. The participants were 21 students. Besides , vocabulary mostly improve after being taught by using picture series. The participants were 21 students from VII SMPN 2 Merbau. This research conducted in three cycles. The data collection technique was obtained through (i) observation sheet which was applied to know the students and teacher performance during the teahing and learning process., (2) test was done to measure students achievement, and (3) field note was obtain information about teacher, the students activities and performances in the teaching and learning process during the implementation of picture series. The research can briefly can briefly explain as follow : first the students speaking ability could be improve by using picture series, before the research was done , the average score of students was only 46.02 in pretest, after thye research was done for cycle 1, it improved to 59.then, in cycle 2 increased up to 66. Second, the onservation shield and field note result showed that the use of picture series make teaching process more effective and it also helped students improve their seaking ability and more active in learning process. This improvement happened because this picture series method is appropriate applied in class.Key Words: Speaking, Ability, Picture series.